Solving Nonlinear Boundary Value Problem Arising of Natural Convection Porous Fin By Using the Haar Wavelet Collocation Method and Temimi and Ansari Method - Abd, Sinan H.; Mohammed, Areej Salah (Iraqi Journal of Science, 2022)
In this article, the boundary value problem of convection propagation through the permeable fin in a natural convection environment is solved by the Haar wavelet collocation method (HWCM). We also compare the solutions with the application of a semi-analytical method , namely the Temimi and Ansari (TAM), that is characterized by accuracy and efficiency.The proposed method is also characterized by simplicity and efficiency. The possibility of applying the proposed method to many types of linear or nonlinear ordinary and partial differential equations.